Morphology and morphometry of mental foramen in dry human mandibles - Bala, Samreen Siraj; Shahdad, Shaheen; Bashir, Shahnawaz (International Journal of Research in Medical Sciences, 2017)
Background: Mental foramen (MF) is an important landmark to facilitate surgical, local anaesthetic and other invasive procedures. The present study was aimed to provide anatomical information on the position, morphological variations and incidence of mental foramen and accessory mental foramen. Methods: This study was conducted on 41 dry adult human mandibles in the department of anatomy, Government Medical College Srinagar, Jammu and Kashmir. Parameters like incidence, position, shape and presence of accessory mental foramen were studied. Results: Mental foramen was present bilaterally in all 41 mandibles. Accessory mental foramen(AMF) was present in 2 cases (4.87%). The most frequent position of foramen in relation to the teeth was in line with the longitudinal axis of 2nd premolar on both right (63.42%) and left (60.98%) side. Most common shape was round shape. Conclusions: Mental foramen variation often remains unnoticed and undiagnosed. Variations do exist in the position, shape, and size of mental foramen in different population groups. Present study provide the necessary data of mental foramen location and morphometry which may be useful for the surgeons, anaesthetists, neurosurgeons and dentists to carry out nerve block and surgical procedures.